International Law and Protection of the Caspian Ecosystem - E. E. Vylegzhanina; D. N. Panasenko (Московский журнал международного права)
An overwhelming international legal act on the status of the Caspian is developed now by the Caspian States. One of the provisions already agreed upon provides for the responsibility of these States for conservation of all the values of the sea for the present and future generations. Main approaches for protection of the sea are formulated in the Frame Convention on the protection of the Caspian environment, developed by States, mostly commercially interested in exploitation of the oil and gas resources of the Caspian Sea. However, it is the oil and gas activity that makes the gravest negative impact on the environment in general, as well as on the sea bottom itself, provoking intensification of the tectonics. This is the factor that makes the adverse influence on the oil and gas facilities increasing the geoecological risks. Integrated management of Caspian resources, taking into consideration all geo and ecological particularities of the region, seems a perspective field of cooperation of the Caspian States.